2019
DOI: 10.3126/jgmcn.v12i2.27149
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Abdomen: Acute Appendicitis

Abstract: Background: Traditionally, appendectomy has been the treatment of choice for acute appendicitis but many times diagnosis can be difficult. Clinicians are looking through different ways to come to the correct diagnosis to decrease negative appendectomy. The aim of this study was to determine relation between clinical pattern, laboratory and ultrasonography findings with histopathological report of appendectomy specimen and to evaluate the Alvarado scoring regarding its usefulness in the early diagnosis in our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In a similar study of Gandaki Medical College Pokhara, out of 1021, 203 (19.88%) were managed conservatively whereas 818 (80.11%) were surgically managed. 11 In our study, 160 (49.84) were managed surgically while 160 (49.84) were managed conservatively. However, Appendectomy, via open laparotomy through a limited right lower quadrant incision or via laparoscopy, is the standard treatment for acute appendicitis.…”
Section: Discussionmentioning
confidence: 69%
“…In a similar study of Gandaki Medical College Pokhara, out of 1021, 203 (19.88%) were managed conservatively whereas 818 (80.11%) were surgically managed. 11 In our study, 160 (49.84) were managed surgically while 160 (49.84) were managed conservatively. However, Appendectomy, via open laparotomy through a limited right lower quadrant incision or via laparoscopy, is the standard treatment for acute appendicitis.…”
Section: Discussionmentioning
confidence: 69%
“…e diagnosis of acute uncomplicated appendicitis depends on history and clinical exam, laboratory investigations, mainly the inflammatory markers triad (leukocytosis, neutrophilia, and C-reactive protein), and imaging, mainly ultrasound, which was done for all patients and CT scan which was done only for query cases (46 patients). 10 * Alvarado score: 0-4: unlikely appendicitis; 5-6: equivocal for appendicitis; 7-8: probably appendicitis; 9-10: most likely appendicitis (Table 1 is from Neupane et al [5] under the Creative Commons Attribution License/Public Domain).…”
Section: Resultsmentioning
confidence: 99%
“… ∗ Alvarado score: 0–4: unlikely appendicitis; 5-6: equivocal for appendicitis; 7-8: probably appendicitis; 9-10: most likely appendicitis ( Table 1 is from Neupane et al [ 5 ] under the Creative Commons Attribution License/Public Domain). …”
Section: Tablementioning
confidence: 99%
“…A large cross-sectional observational study by Neupane et al . in 2019 53 with 1021 patients suggested that AS is significantly higher in patients with AA as compared to patients with other diseases. They identified the large variation in presentation, severity of disease, radiological work-up, and surgical management of AA.…”
Section: Discussionmentioning
confidence: 96%
“…The classification of AS was different in every study, which made statistical modeling more difficult. Some of the studies 51 46 , 53 have calculated AS retrospectively, which underestimates the true performance of AS (raises the possibility of performance bias). Variables collected in each study were different from one another, and there was a lot of missing data when we combined the data, leading to statistical heterogeneity.…”
Section: Discussionmentioning
confidence: 99%